Gallery Tour Strategy to Increase the Number of Visitors at Tirtodipuran Gallery Link Yogyakarta - Agustina Magdalena (Publikasi Indonesia, 2024)
The strategy to increase the number of visitors to galleries and museums is now still a burden for managers. The promotion strategy used by the manager should not stand alone or continue to use the most effective promotion mix (promotion mix) carried out by the analysis of the strengths and advantages of each gallery or museum. One form in the promotional mix that can still be used is word-of-mouth information which has been proven to be effective because it focuses on visitor satisfaction and loyalty as the target market for art galleries. However, WOM also cannot stand alone without the help of other forms of promotion such as advertising and public relations. This study aims to provide information about the effectiveness of gallery tours as a promotional strategy to increase the number of visitors to the gallery. The method used is qualitative with a descriptive approach. The data collection technique is by observation, interviews, and documentation carried out directly by researchers at the research location, namely the Tirtodipuran Link Yogyakarta gallery from October to December 2023. The results of the study show that visitors are impressed by the existence of gallery tours, so gallery tours can be a form of promotion, namely WOM and the increase in the number of visitors can also be evidenced through visitor data that shows an increase in certain months when the gallery holds the opening of exhibitions and artist workshops in which there are gallery tour activities in it. So the conclusion obtained from this study is that gallery tour services can not only create visitor satisfaction and loyalty but also can be a form of promotion in the form of WOM to increase the number of visitors to the gallery and it is hoped that this promotion strategy can also be applied in national museums in Indonesia.